Pemodelan Sebaran Sistem Hidrotermal dan Identifikasi Jenis Batuannya dengan Metode CSAMT (Studi Kasus Gunungapi Ungaran) - Hadi, Arif Ismul; Brotopuspito, Kirbani Sri; Wahyudi, Wahyudi (Lambung Mangkurat University Press, 2009)
The investigation of the hydrothermal system distribution andidentification of its rock type has been done by CSAMT method at Ungaran Volcano area. The acquisition data has been done around 750 m x 100 m area with 4 lines at N750E direction. Sounding site distanced 250 m, whereas the data was measured by Stratagem model 26716-01 Rev.D. Processing of the data wasstarted by 1-D inversion of Robust method. The 1-D results were then used as the input of MT2D software. The results showed that subsurface resistivity were 8.6 to 46.4 Î©m estimated as hydrothermal system, 55.8 to 102.6 Î©m estimated as aquifer zone or permeable saturated zone, 145.3 to 495.7 Î©mÂ stimated as pra-caldera rock associated with vapor dominated zone, and 1420.5 to 15.083 Î©m estimated as lava pile associated with basaltic and andesitic rock. The most prospective hydrothermal system area existed at all along line 4 on 30 to 140 m depth.